DETERMINAN KEJADIAN STUNTING PADA BALITA DI WILAYAH KERJA PUSKESMAS SIMPANG TIGA KABUPATEN PIDIE TAHUN 2019 - Ramadhaniah; Fajar Misbahul Fuady; Syarifuddin Anwar (Politeknik Negeri Jember, 2021)
Stunting is a condition of malnutrition (Z-Score = <- 2 SD) which occurs continuously and occurs for a long time. In 2018 Pidie district was in the fourth highest position (38%) related to the incidence of stunting in Aceh province after Aceh Tenggara district (66.9%), Aceh Barat Daya district (60.9%) and Gayo Lues district (59, 5%). This study aims to determine the risk factors for stunting in children under five in the working area of the Simpang Tiga Public Health Center, Pidie Regency in 2019. This research is a descriptive analytic study with cross sectional design. The sample in this study were all mothers who have stunting toddlers aged 0-59 months who live in the working area of the Simpang Tiga Public Health Center. Sampling was done by using a total population method of 94 respondents. Data were analyzed by univariate, bivariate with chi square test and multivariate using multiple logistic regression. From the results of the study, it was found that as many as (19.1%) children were stunted in the very short category, those with low birth weight babies (18.1%), who had a history of infectious diseases (30.9%), who had poor eating habits. good (35.1%), those with poor immunization status (24.5%), those with low protein levels (14.9%) and those with low energy levels (11.7%). From statistical analysis it can be concluded that there is a relationship between birth weight (p = 0.003), dietary care (p = 0.022), immunization status (p = 0.001), protein adequacy level (p = 0.025), energy adequacy level (p = 0.006) and there was no association with a history of infectious disease (0.265) with stunting in children under five. The logistic regression test results showed that immunization status was the most influential risk factor for the incidence of stunting (OR = 8.2), 95% CI: 2,323-28,850. It is hoped that Simpang Tiga Public Health Center officers can improve counseling and socialization and try to provide understanding for parents about the importance of immunization so that it can reduce stunting in toddlers in the future. Keywords: Stunting, Risk Factors, Toddlers